Respuesta :

Answer:

y-6 = -3(x+1)

Step-by-step explanation:

The point-slope form of a line is the following:

y-yo = m(x-xo), where 'm' is the slope and (xo, yo) is any point where the line passes through.

In this case, m=-3 and (xo, yo) = (-1, 6).

Therefore: y-yo = m(x-xo) = y-6 = -3(x+1)

In conclusion, the point-slope form of the equation that represents the line that passes through the point (-1, 6) and has a slope of -3 is:

y-6 = -3(x+1)

For this case we have that the equation of a line in the point-slope form is given by:

[tex](y-y_ {0}) = m (x-x_ {0})[/tex]

Where:

m: It's the slope

[tex](x_ {0}, y_ {0})[/tex]: It is a point through which the line passes

According to the data we have to:

[tex]m = -3\\(x_ {0}, y_ {0}) = (- 1,6)[/tex]

So the equation is:

[tex](y-6) = - 3 (x - (- 1))\\(y-6) = - 3 (x + 1)[/tex]

Answer:

[tex](y-6) = - 3 (x + 1)[/tex]